2019
DOI: 10.3390/molecules24234300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antifungal Phenolics from Helianthus tuberosus L. Leaves against Phytophthora capsici Leonian by Chemometric Analysis

Abstract: Phytophthora capsici Leonian causes destructive economical losses in pepper production, and a promising source of natural fungicides- Helianthus tuberosus leaves was reported. The antifungal activities of different extracts and compounds from H. tuberosus leaves against the phytopathogen, P. capsici Leonian, were examined by chemometric analysis, including HPLC-MS/MS and multivariate data analyses. Principal component analysis and orthogonal partial least squares-discriminate analysis were applied to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…[15][16][17][18] In recent years, plant metabolites with antifungal properties have attracted increasing attention because of their natural biodegradation and low toxicity to humans and animals. [19][20][21][22] Plant essential oils have minimal impact on non-target organisms and the environment, and are recommended in many integrated pest management programs to protect plants against pests and diseases. For example, the essential oils used on Frankliniella occidentalis Perg were obtained from Mentha pulegium and Thymus mastichina, with 50% (and 90%) lethal concentration values of 3.1 (3.8) and 3.6 (4.6) mg L −1 air, respectively; essential oils of M. spicata, M. piperita, T. vulgaris chemotype (CT) carvacrol and T. vulgaris chemotype (CT) thymol inhibited the mycelial growth of Rhizopus stolonifer with inhibition rates of 92.4%, 98.0%, 98.5%, and 9.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In recent years, plant metabolites with antifungal properties have attracted increasing attention because of their natural biodegradation and low toxicity to humans and animals. [19][20][21][22] Plant essential oils have minimal impact on non-target organisms and the environment, and are recommended in many integrated pest management programs to protect plants against pests and diseases. For example, the essential oils used on Frankliniella occidentalis Perg were obtained from Mentha pulegium and Thymus mastichina, with 50% (and 90%) lethal concentration values of 3.1 (3.8) and 3.6 (4.6) mg L −1 air, respectively; essential oils of M. spicata, M. piperita, T. vulgaris chemotype (CT) carvacrol and T. vulgaris chemotype (CT) thymol inhibited the mycelial growth of Rhizopus stolonifer with inhibition rates of 92.4%, 98.0%, 98.5%, and 9.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It was found to be 21.03 ± 0.97 mg QE/g for Ht-EAF, 19.85 ± 0.21 mg QE/g for Ht-ME, 11.48 ± 0.11 mg QE/g for Ht-HF, and 6.27 ± 1.09 mg QE/g for Ht-MF. Taken together, the findings of the phytochemical quantifications in H. tuberosus revealed that phenols and flavonoids are abundantly present in the fractions that are responsible for its therapeutic potentials [ 29 , 30 , 31 ]. Moreover, the total flavonoid content was significantly lower than the total phenolic content.…”
Section: Resultsmentioning
confidence: 99%
“…The final collection rate of the organic extract was the lowest out of all the extracts, which is why quite a large amount of Jerusalem artichoke powder is required to identify organic extracts, which is costly and labor intensive. It is presumable that it consisted of lipids, such as essential oils, sesquiterpenes, and caffeoylquinic acids [ 52 , 53 ], based on current evidence. Additionally, previous research has noted that caffeoylquinic acids can increase Bifidobacterium levels [ 54 ], so it is possible that this essential oil, in particular, affected microbiota composition.…”
Section: Discussionmentioning
confidence: 99%